Determination of the Maxwell-Boltzmann Distribution Probability for Different Gas Mixtures - Ibrahim Kaittan Fayyadh; Harith Abd-Al razak Hassan; Muhammad Asmail Eleiwi; Farhan Lafta Rashid (Engineering and Technology Journal, 2014)
From the Maxwell speed distribution can be calculated several characteristic molecular speeds, namely, the most probable speed νp , the mean speed , and the root-mean-square speed νrms , furthermore satisfy the condition of speed for percentage different gaseous mixtures at 3000K. The obtained results have been drawn as functions for its variables and appeared in good agreement with the literature.